2019
DOI: 10.21037/jtd.2019.09.56
|View full text |Cite
|
Sign up to set email alerts
|

Survival and late toxicities following concurrent chemo-radiotherapy for locally advanced stage III non-small cell lung cancer: findings of a 10-year Australian single centre experience with long term clinical follow up

Abstract: Background: The preferred management of patients with unresectable locally advanced non-small cell lung cancer (LA-NSCLC) is concurrent chemo-radiotherapy (CRT). Acute CRT-related toxicities are well defined, however, less is known about late toxicities. The aim of the study was to examine the outcomes and late toxicities in Stage III NSCLC treated with CRT. Methods: A retrospective review of the data from patients with stage III NSCLC treated with CRT was performed between May 2000 and June 2010. Demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…The main progress of the treatment for NSCLC includes immunotherapy and targeted therapy. Historically, the standard treatment f o r p a t i e n t s w i t h u n r e s e c t a b l e l o c a l l y a d v a n c e d NSCLC (LA-NSCLC) was platinum-based concurrent chemoradiotherapy (2). However, prognosis has been poor, with a 5-year overall survival (OS) rate ranging from 15% to 25%, and the median OS time only 17-24 months (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The main progress of the treatment for NSCLC includes immunotherapy and targeted therapy. Historically, the standard treatment f o r p a t i e n t s w i t h u n r e s e c t a b l e l o c a l l y a d v a n c e d NSCLC (LA-NSCLC) was platinum-based concurrent chemoradiotherapy (2). However, prognosis has been poor, with a 5-year overall survival (OS) rate ranging from 15% to 25%, and the median OS time only 17-24 months (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Another study was conducted across two continents simultaneously (North America and Europe) [27]. The rest of the studies were only conducted in one country on the following continents: one in North America [26], one in Europe [25], two in Asia [24,28], and one in Australia [22]. Eight studies were cohort studies [20-24, 26, 28, 29], whereas the others were randomized trials [2,25,27].…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles did not report the settings of the studies [2,21,[23][24][25][26]29] but when cited, most were performed in hospitals. Two studies [20,28] were completed in and used data exclusively from hospital healthcare settings, while the other two [22,27] were conducted in two healthcare settings simultaneously (outpatient and hospital).…”
Section: Resultsmentioning
confidence: 99%
“…It can significantly impact physical and psychological wellbeing, and its management can become complex and multifactorial [ 3 ]. There are numerous reports of dysphagia and appetite loss in cancer patients (stomach, colorectal, lung, breast, and head/neck) [ 4 , 5 , 6 , 7 , 8 ]. Moreover, Jacqui et al reported the proportion of patients with 14 types of cancers who reported dysphagic symptoms as follows: any dysphagia (54%), dysphagia for liquids (20%), and dysphagia for solids (46%).…”
Section: Introductionmentioning
confidence: 99%